Transcriptomic analysis of the Myxococcus xanthus FruA regulon, and comparative developmental transcriptomic analysis of two fruiting body forming species, Myxococcus xanthus and Myxococcus stipitatus - Anna L. McLoon (BMC, 2021)
Abstract Background The Myxococcales are well known for their predatory and developmental social processes, and for the molecular complexity of regulation of these processes. Many species within this order have unusually large genomes compared to other bacteria, and their genomes have many genes that are unique to one specific sequenced species or strain. Here, we describe RNAseq based transcriptome analysis of the FruA regulon of Myxococcus xanthus and a comparative RNAseq analysis of two Myxococcus species, M. xanthus and Myxococcus stipitatus, as they respond to starvation and begin forming fruiting bodies. Results We show that both species have large numbers of genes that are developmentally regulated, with over half the genome showing statistically significant changes in expression during development in each species. We also included a non-fruiting mutant of M. xanthus that is missing the transcriptional regulator FruA to identify the direct and indirect FruA regulon and to identify transcriptional changes that are specific to fruiting and not just the starvation response. We then identified Interpro gene ontologies and COG annotations that are significantly up- or down-regulated during development in each species. Our analyses support previous data for M. xanthus showing developmental upregulation of signal transduction genes, and downregulation of genes related to cell-cycle, translation, metabolism, and in some cases, DNA replication. Gene expression in M. stipitatus follows similar trends. Although not all specific genes show similar regulation patterns in both species, many critical developmental genes in M. xanthus have conserved expression patterns in M. stipitatus, and some groups of otherwise unstudied orthologous genes share expression patterns. Conclusions By identifying the FruA regulon and identifying genes that are similarly and uniquely regulated in two different species, this work provides a more complete picture of transcription during Myxococcus development. We also provide an R script to allow other scientists to mine our data for genes whose expression patterns match a user-selected gene of interest.